Anti-inflammatory effect of hesperidin enhances chondrogenesis of human mesenchymal stem cells for cartilage tissue repair - Shipeng Xiao; Wenguang Liu; Jianqiang Bi; Shenghou Liu; Heng Zhao; Ningji Gong; Deguo Xing; Hongwei Gao; Mingzhi Gong (BMC, 2018)
Abstract Background Articular cartilage diseases are considered a major health problem, and tissue engineering using human mesenchymal stem cells (MSCs) have been shown as a promising solution for cartilage tissue repair. Hesperidin is a flavonoid extract from citrus fruits with anti-inflammatory properties. We aimed to investigate the effect of hesperidin on MSCs for cartilage tissue repair. MSCs were treated by hesperidin, and colony formation and proliferation assays were performed to evaluate self-renewal ability of MSCs. Alcian blue staining and Sox9 expression were measured to evaluate chondrogenesis of MSCs. Secretion of pro-inflammatory cytokines IFN-γ, IL-2, IL-4 and IL-10, and expression of nuclear factor kappa B (NF-κB) subunit p65 were also assessed. Results Hesperidin improved self-renewal ability and chondrogenesis of MSCs, inhibited secretion of pro-inflammatory cytokines IFN-γ, IL-2, IL-4 and IL-10, and suppressed the expression of p65. Overexpression of p65 was able to reverse the hesperidin inhibited secretions of pro-inflammatory cytokines, and abolish the enhancing effect of hesperidin on chondrogenesis of MSCs. Conclusion Hesperidin could serve as a therapeutic agent to effectively enhance chondrogenesis of human MSCs by inhibiting inflammation to facilitate cartilage tissue repair.